AB0778 ASSOCIATION BETWEEN PATIENT-REPORTED OUTCOMES AND DISEASE ACTIVITY IN BIMEKIZUMAB-TREATED PATIENTS WITH PSORIATIC ARTHRITIS. (2nd June 2020) - Gossec, L.; Mease, P. J.; Gottlieb, A. B.; Ogdie, A.; Assudani, D.; Coarse, J.; Ink, B.; Coates, L. C.
Abstract : Background: Bimekizumab (BKZ) is a humanised IgG1 monoclonal antibody, which selectively neutralises interleukin (IL)-17A and IL-17F. There is support for the BKZ mechanism of action as a novel therapeutic approach for psoriatic arthritis (PsA). 1-3 The phase 2b dose-ranging BE ACTIVE study assessed the efficacy and safety of BKZ in patients (pts) with PsA; data are reported elsewhere. 4 Patient-reported outcomes (PROs) are increasingly recognised as important endpoints in clinical trials. 5 The Psoriatic Arthritis Impact of Disease-9 (PsAID-9) questionnaire was specifically developed to assess health-related quality of life (QoL) in pts with PsA 5 and its validity in clinical practice has been demonstrated. 5-6 Objectives: To report the association between PsAID-9 score (a PRO) and disease activity response (very low disease activity [VLDA], minimal disease activity [MDA] or Disease Activity Index for Psoriatic Arthritis [DAPSA] remission) during 48 weeks' (wks') BKZ treatment. Methods: Details of the study design (NCT02969525 ) are reported elsewhere. 4 Here, we report the proportion of pts who achieved a PsAID-9 score ≤3, and the association between PsAID-9 score at Wk 48 (range 0–10, where 10 corresponds to worst QoL) and VLDA/MDA (binary states of disease control) or DAPSA (range 0–>28 where 0–4 is remission, 5–14 is low, 15–28 is moderate, and >28 is high disease activity) at Wk 12. Results: Across 206 randomised pts at baseline, 66.5% had psoriasis body surface area (BSA) ≥3%, 18.9% had prior tumour necrosis factor inhibitor (TNFi) exposure, and 63.6% received concomitant methotrexate. A substantial proportion of pts achieved MDA and/or DAPSA remission by Wk 12, which generally increased through to Wk 24 and 48 (Table 1 ). The 160 mg BKZ group saw the highest Wk 48 rates of MDA response (60.0%) and DAPSA remission (45.0%) (Table 1 ). The proportion of pts achieving a PsAID-9 score ≤3 was consistently high across all active treatment arms (Figure 1 ). PsAID-9 score was consistently lower (indicating better QoL) for pts with VLDA or MDA, and those in DAPSA remission (Figure 2 ), indicating that low disease activity was associated with improved PROs. Conclusion: In BKZ-treated pts, improvements in PsAID-9 were associated with achievement of VLDA/MDA response and DAPSA remission. These results suggest that pts achieving higher disease control have improved QoL. References: [1] Glatt S. Ann Rheum Dis 2018;77:523–32; 2. Glatt S. Br J Clin Pharmacol 2017;83:991–1001; 3. Papp KA. J Am Acad Dermatol 2018;79:277–86; 4. Ritchlin CT. Ann Rheum Dis 2019;78:127–8; 5. Gossec L. Ann Rheum Dis 2014;73:1012–19; 6. Johnson K. Semin Arthritis Rheum 2019;49:241–45. Acknowledgments: This study was funded by UCB Pharma. Editorial services were provided by Costello Medical. Disclosure of Interests: Laure Gossec Grant/research support from: Lilly, Mylan, Pfizer, Sandoz, Consultant of: AbbVie, Amgen, Biogen, Celgene, Janssen, Lilly, Novartis, Pfizer, Sandoz, Sanofi-Aventis, UCB, Philip J Mease Grant/research support from: Abbott, Amgen, Biogen Idec, BMS, Celgene Corporation, Eli Lilly, Novartis, Pfizer, Sun Pharmaceutical, UCB – grant/research support, Consultant of: Abbott, Amgen, Biogen Idec, BMS, Celgene Corporation, Eli Lilly, Novartis, Pfizer, Sun Pharmaceutical, UCB – consultant, Speakers bureau: Abbott, Amgen, Biogen Idec, BMS, Eli Lilly, Genentech, Janssen, Pfizer, UCB – speakers bureau, Alice B Gottlieb Grant/research support from:: Research grants, consultation fees, or speaker honoraria for lectures from: Pfizer, AbbVie, BMS, Lilly, MSD, Novartis, Roche, Sanofi, Sandoz, Nordic, Celltrion and UCB., Consultant of:: Research grants, consultation fees, or speaker honoraria for lectures from: Pfizer, AbbVie, BMS, Lilly, MSD, Novartis, Roche, Sanofi, Sandoz, Nordic, Celltrion and UCB., Speakers bureau:: Research grants, consultation fees, or speaker honoraria for lectures from: Pfizer, AbbVie, BMS, Lilly, MSD, Novartis, Roche, Sanofi, Sandoz, Nordic, Celltrion and UCB., Alexis Ogdie Grant/research support from: Pfizer to Penn, Novartis to Penn, Amgen to Forward/NDB, Consultant of: Abbvie, Amgen, Bristol-Myers Squibb, Celgene, Corrona, Janssen, Eli Lilly, Novartis, Pfizer, Deepak Assudani Employee of: UCB Pharma, Jason Coarse Employee of: UCB Pharma, Barbara Ink Shareholder of: GlaxoSmithKline and UCB Pharma, Employee of: UCB Pharma, Laura C Coates: None declared